2003
DOI: 10.1159/000072088
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of Peroxisome-Proliferator Activated Receptor-Gamma Reduce Renal Ischemia/Reperfusion Injury

Abstract: Background/Aims: Recent evidence indicates that peroxisome-proliferator activated receptor (PPAR) agonists protect against ischemia/reperfusion (I/R) injury. Here we investigate the effects of the PPAR-γ agonists, rosiglitazone and ciglitazone, on the renal dysfunction and injury caused by I/R of the rat kidney in vivo. Methods: Rosiglitazone or ciglitazone were administered to male Wistar rats prior to and during reperfusion. Biochemical indicators of renal dysfunction and injury were measured and histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(145 citation statements)
references
References 24 publications
11
130
2
2
Order By: Relevance
“…[2] However, reperfusion can paradoxically create more tissue injury by initiating the complex cellular events that result in renal injury and the concluding death of renal cells due to a combination of apoptosis and necrosis. High levels of oxygen free radicals produced on reperfusion play a critical role in the injury caused by I/R.…”
Section: Introductionmentioning
confidence: 99%
“…[2] However, reperfusion can paradoxically create more tissue injury by initiating the complex cellular events that result in renal injury and the concluding death of renal cells due to a combination of apoptosis and necrosis. High levels of oxygen free radicals produced on reperfusion play a critical role in the injury caused by I/R.…”
Section: Introductionmentioning
confidence: 99%
“…The observed protection has been attributed to improved insulin sensitivity and glucose metabolism and reduced inflammation and apoptosis in the kidneys. 15d-PGJ2 was also shown to protect the kidneys from ischemic injury by inhibiting NF-kappaB activation and other pro-inflammatory proteins like AP-1, ICAM1 and iNOS, thereby decreasing oxidative stress (23,95,96) (Table 3). …”
mentioning
confidence: 99%
“…Several experimental studies in rats showed favorable effects of PPAR-␥ agonism on nondiabetic renal pathology (24), including anti-glomerular basement membrane antibody-induced crescentic glomerulonephritis (8), passive Heymann nephritis (2), the development of glomerulosclerosis after 5/6 nephrectomy (12), and renal ischemia-reperfusion induced damage (26). The course of anti-Thy1-glomerulonephritis is determined by the degree of inflammatory cell invasion and inflammatory damage (4), as well as by the degree of endothelial repair (15).…”
Section: Discussionmentioning
confidence: 99%